Management and Follow-Up of a Case of Gestational Gigantomastia in a Brazilian Hospital - Pollyana Eler dos Reis; Natalia Quarto Blunck Santos; Fernanda Alves Barbosa Pagio; Fabio Chambô; Danielle Chambô; Antônio Chambô Filho (Hindawi Limited, 2014)
Gigantomastia is a breast disorder that is associated with an exaggerated, rapid growth of the breasts, generally bilaterally. Since the pathology is rare and has seldom been described, its etiology has yet to be fully established, although there are speculations that a hormonal component may play an important role. Treatment is aimed at improving the clinical and psychological symptoms; however, the best therapeutic option varies from case to case. The present report describes a case of gestational gigantomastia seen at the Department of Obstetrics and Gynecology of the Hospital da Santa Casa de Misericórdia, Vitória, Espírito Santo, Brazil, in a primigravida in the second trimester of pregnancy. The report follows this patient from her diagnosis until the completion of treatment with a third and final surgical procedure.